FRI0203 The link between copd and ankylosing spondylitis: a population based study. (12th June 2018) - Sharif, K.; Watad, A.; Tiosano, S.; Yavne, Y.; Comanehster, D.; Cohen, A.; Amital, H.
Abstract : Background: Ankylosing spondylitis (AS) is one of the most common and severe subtypes of the spondyloarthropathies. Extra-articular involvement among AS patients, including lung disease, has been described widely. Chronic obstructive pulmonary disease (COPD) has been linked to several autoimmune diseases, however, very few studies have investigated the association between AS and COPD. Objectives: To assess whether an association exists between AS and COPD. Methods: A population-based cross-sectional study was conducted using data retrieved from the largest electronic medical records database in Israel, the Clalit Health Services (CHS). Patients were defined as having AS or COPD when there was at least one such documented diagnosis in their medical records. The proportion of COPD was compared between AS patients and controls. A logistic regression model was used to estimate the association between AS and COPD in a multivariate analysis adjusted for age, gender and smoking status Results: The study included 4076 patients with AS and 20 290 age- and sex-frequency matched controls. The proportion of COPD in AS patients was higher than in controls (46% vs. 18%, respectively, p<0.001). Multivariate logistic regression demonstrated a robust independent association between AS and COPD (OR 1.225, p=0.031). Conclusions: Our study supports an association between AS and COPD, further extending the link between COPD and autoimmune diseases. This finding highlights the importance of smoking cessation in AS patients and raises the question of whether COPD screening may be warranted. Disclosure of Interest: None declared